Synthesis of precipitated calcium carbonate using chicken bones as a raw material for paper - Erlinda, Riska Melati; Rahma Putri Salsabila; Suprihatin (Jurnal Penelitian Saintek, 2025)
This research discusses the synthesis of precipitated calcium carbonate (PCC) standard for raw paper materials from chicken bones. In the paper industry, PCC is used as a coating and filler to enhance paper's smoothness, brightness, and opacity. The primary material used in this research is chicken bones from the frozen food industry waste, solving environmental problems. Chicken bones were dried in an oven at 100°C, then crushed and sieved to 100 mesh. X-ray Fluorescence (XRF) analysis shows that chicken bones contain calcium at 98.83%. The high content can make chicken bones a raw material for PCC. This research uses variables of Na₂CO₃ solution and precipitation time with a temperature of 30°C.  The target of this research to produce high quality Precipitated Calcium Carbonate (PCC) with a calcite crystal structure suitable for industrial applications particularly as raw material for the paper industry. Based on the analysis results, the best conditions were obtained at a Na₂CO₃ concentration of 2.5 M and a precipitation time of 40 minutes. The XRF and XRD test analyses showed that PCC was a polymorph calcite with a particle size of 2.14752 µm. This research proves that chicken bones can be an alternative raw material for PCC by ISO 3262-2:1998 parameters for industry standards